Business models in the area of logistics in search of hidden champions, their business principles and common industry misperceptions - Neubauer, Regina M.; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
The significance of managing end-to-end supply chains from one hand has been the subject of discussion for over ten years. Regina M. Neubauer provides an answer on how such a scenario might work by studying small- and medium-sized enterprises in the European logistics industry based on her Business Model Performance Scoring Framework. She proves that small- and medium-sized enterprises in logistics are sustainable, i.e. she identifies Hidden Champions that are successful partners in a collaborative business model by offering individualized solutions.
Fundamentals, Developments and Demography of Logistics; Business Analysis and Business Model Architectures; Business Model Performance Scoring Framework; Collaborative Business Modeling
Electronic reproduction.
Keywords: Electronic books